POLITICS, RESEARCH AGENDAS AND ABORTIVE FIELDWORK PLANS OVER LYKTOS, CRETE: A HISTORY OF ARCHAEOLOGICAL RESEARCH. (November 2019) - Kotsonas, Antonis
Abstract : Politics and research agendas have had a major role in shaping the archaeology of Crete. This article focuses on the history of research on Lyktos, one of the most important ancient cities of the island, to explore the impact of academic and non-academic factors on archaeological fieldwork. Relying on wide-ranging archival research and extending from the Renaissance to the early twenty-first century, the analysis covers the fluctuation of international scholarly interest in Lyktos, the often abortive plans for excavations by numerous British, Italian, German and Greek archaeologists, and the ways in which fascination with the ancient city relates to broader political and disciplinary history. I also synthesise the small-scale fieldwork conducted at the site and reconstruct its archaeological landscape from the Bronze Age to the Medieval period, offering several new insights in local topography and material culture. This work challenges the characterisation of Lyktos as a 'phantom city' and highlights the significance of the site for the archaeology of Crete. Abstract : Πολιτικές διεργασίες, ερευνητικές προτεραιότητες και ανεπιτυχείς προσπάθειες για την ανασκαφή της Λύκτου στην Κρήτη: Ιστορία της αρχαιολογικής έρευνας Πολιτικές διεργασίες και ερευνητικές προτεραιότητες έχουν συντελέσει καθοριστικά στη διαμόρφωση της αρχαιολογίας της Κρήτης. Το άρθρο αυτό επικεντρώνεται στην ιστορία της έρευνας στη Λύκτο, μία από τις σπουδαιότερες αρχαίες πόλεις του νησιού, προκειμένου να μελετήσει τον αντίκτυπο ακαδημαϊκών και εξω-ακαδημαϊκών παραγόντων στο αρχαιολογικό έργο. Βασισμένο σε ευρεία αρχειακή έρευνα και εκτεινόμενο από την περίοδο της Αναγέννησης ως τις μέρες μας, το άρθρο αναδεικνύει τη διακύμανση του διεθνούς επιστημονικού ενδιαφέροντος για τη Λύκτο, τα συχνά ανεπιτυχή σχέδια Βρετανών, Ιταλών, Γερμανών και Ελλήνων αρχαιολόγων να ανασκάψουν τη θέση, καθώς και τον αντίκτυπο ευρύτερων πολιτικών και ερευνητικών εξελίξεων στο ενδιαφέρον για την αρχαία πόλη. Επιπλέον, το άρθρο εξετάζει συνδυαστικά τις περιορισμένες ανασκαφικές έρευνες που έχουν διεξαχθεί στη Λύκτο και ανασυνθέτει το αρχαιολογικό της τοπίο από την Προϊστορική ως τη Μεσαιωνική περίοδο στη βάση πρωτότυπων παρατηρήσεων για την τοπογραφία και τον υλικό της πολιτισμό. Η έρευνα αυτή θέτει υπό αμφισβήτηση τον χαρακτηρισμό της Λύκτου ως ῾πόλης–φαντάσματος᾽ και αναδεικνύει τη σημασία της θέσης για την αρχαιολογία της Κρήτης.